2021
DOI: 10.1108/aeds-05-2020-0100
|View full text |Cite
|
Sign up to set email alerts
|

Students' readiness for e-learning during the COVID-19 pandemic in a South-East Asian university: a Rasch analysis

Abstract: PurposeUniversities have shifted from face-to-face learning environments to e-learning in response to the COVID-19 pandemic. However, the sudden change to online teaching has raised concerns among lecturers about students' readiness for e-learning. This study investigates students' readiness for e-learning during the COVID-19 pandemic and specifically assesses any significant differences between students' gender, age, ethnicity, level of education, field of study and their readiness for an e-learning environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 32 publications
4
45
1
Order By: Relevance
“…On the contrary, the finding shows that technology readiness of MSCE examiners is not the same across the age groups. A similar result was found by Chen, Li, Liu, Yen Adams, Chuah, Bambang and Mohamed (2021). Thus, in these separate studies young participants were found to be more technologically ready than old ones.…”
Section: Discussionsupporting
confidence: 85%
“…On the contrary, the finding shows that technology readiness of MSCE examiners is not the same across the age groups. A similar result was found by Chen, Li, Liu, Yen Adams, Chuah, Bambang and Mohamed (2021). Thus, in these separate studies young participants were found to be more technologically ready than old ones.…”
Section: Discussionsupporting
confidence: 85%
“…Another point is that students under 20 years old can obtain information quickly using the internet, but they prefer face-to-face. Bachelor's students tend to be easily distracted during online learning and need extra assistance in using the technology during the learning process (Adams et al, 2021).…”
Section: Online Educational Level and Online Learning Successmentioning
confidence: 99%
“…Before responding, students are allowed to choose whether to continue taking the survey or not. Student participation is voluntary and anonymous [39]. We assume that all data collected are responses given without coercion.…”
Section: Research Proceduresmentioning
confidence: 99%